ASPEK HERMENEUTIKA TAFSIR AL-QUR’AN: Studi Kitab Tafsir Jalalain - Rusli, Rusli; Yunus, Muhammad (STAI Darul Kamal NW Kembang Kerang, 2021)
Al-Qur'an always fits in every time and place, in the development of human life it seems as if it challenges the Qur'an to remain the same and go together, so Hermeneutics is promoted to be one of the methods in interpreting it. This thesis study aims to answer two problems, namely how the Hermeneutics method in Jalalain's interpretation and the form of Hermeneutics analysis in Jalalain's interpretation. This research is a library research, and uses the hermeneutic-analytic method, namely by analyzing the data in the hermeneutic circle and then drawing various conclusions. The data to be obtained will be analyzed in accordance with scientific theories with the guidelines provided in the analysis guidelines and in accordance with the rules of writing scientific papers. The results showed that the hermeneutic method in Jalalain's Tafsir in interpretation cannot be separated from three elements, namely: text, author, and reader. So the form of interpretation that results does not only rely on the sound of the text but places more emphasis on the analysis of the verses of the Qur'an related to the use of hermeneutics in Jalalain's Tafsir.